2021
DOI: 10.1155/2021/5538150
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Clinical Effects and Frequency of MEFV Gene Mutation in Patients with Inflammatory Bowel Disease

Abstract: Background. The clinical and pathological features of inflammatory bowel disease (IBD) and Familial Mediterranean Fever (FMF) are similar. Objective. Here, the frequency of Mediterranean Fever (MEFV) gene mutation and its effect on the outcome of IBD were evaluated. Methods. DNA sequence analysis detected the variants on the MEFV gene in patients with IBD. The relationship between mutations and the need for steroids, immunomodulators, biologics, and surgery was assessed. Results. We evaluated 100 patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
(21 reference statements)
0
6
0
Order By: Relevance
“…Therefore, in view of the frequent occurrence of FMF in the population at risk, several authors have called for the inclusion of genetic screening for FMF in the investigation of IBD children of Mediterranean ancestry who display unexplained recurrent isolated fever or other atypical FMF manifestations (repeated tonsilitis in early childhood and isolated arthralgia/myalgia, etc.) ( 20 , 40 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, in view of the frequent occurrence of FMF in the population at risk, several authors have called for the inclusion of genetic screening for FMF in the investigation of IBD children of Mediterranean ancestry who display unexplained recurrent isolated fever or other atypical FMF manifestations (repeated tonsilitis in early childhood and isolated arthralgia/myalgia, etc.) ( 20 , 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, some authors suggest that the environment also affects the phenotype of a monogenic disease of the innate inflammatory pathway ( 44 ). The concomitant presence of MEFV mutations in diseases other than FMF may modify their presence and severity ( 20 , 36 , 40 , 43 ). Particularly, recent studies have revealed an increasing spectrum of rare monogenetic diseases, which can present with IBD or IBD-like intestinal inflammation, particularly with VEO IBD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most pathogenic MEFV variants are missense substitutions leading to inappropriately elevated or prolonged inflammatory responses, though controversy remains over pathogenicity criteria [76][77][78]. Many studies have proposed a link between MEFV variants and GI inflammation [79][80][81][82][83][84][85][86] -with some identifying FMF patients presenting with GI phenotypes "mistaken" for IBD [87][88][89][90][91][92] and others reporting MEFV variants that may influence risk or contribute to IBD pathogenesis [93][94][95][96][97]. A recent systematic review and meta-analysis found that MEFV mutated alleles were more frequently found in IBD patients vs controls, with Exon 10 variants (like our patient's) having the most severe impact [98].…”
Section: Families Without Definitive Diagnosesmentioning
confidence: 99%
“…Patient cohorts have also shown that FMF mutation carriers could be predisposed to other inflammatory diseases independently of FMF [ 14 ]. p.E148Q specifically has been associated with IgA vasculitis [ 15 , 16 ], Ulcerative Colitis and the need for surgery [ 17 ], Crohn’s disease and perianal injury [ 18 ], a stricturing disease pattern, and extra-intestinal disease [ 19 ]. It has also been shown to increase the risk of developing AA amyloidosis alone or in combination with other autoinflammatory diseases (AID) causing mutations [ 20 ].…”
Section: Introductionmentioning
confidence: 99%